Mothering children with developmental disabilities: A critical perspective on health promotion. Issue 6 (3rd June 2017) - Khanlou, Nazilla; Mustafa, Nida; Vazquez, Luz Maria; Davidson, Deborah; Yoshida, Karen
ABSTRACT: We present findings of a qualitative study exploring what constitutes relevant health promotion initiatives for immigrant mothers of children with developmental disabilities. We apply a social ecological approach, with a focus on gender-specific and transformative health promotion, to examine factors impacting mothers' health and wellbeing. Twenty-eight semi-structured and open-ended interviews were conducted with immigrant mothers in the greater Toronto area, Canada. Mothers identified facilitators, challenges, and strategies for their health promotion, providing relevant insights for meaningful intervention. Our findings show that immigrant mothers' health is influenced by intersecting social determinants of health, including migration status, gender, and disability.